COMPRESSED ELEMENTS WITH A VARIABLE IN LENGTH STIFFNESS EQUILIBRIUM FORM STABILITY DETERMINATION - Shkurupiy, Oleksandr; Mytrofanov, Pavlo; Davydenko, Yuriy; Hajiyev, Muhlis (Academic journal Industrial Machine Building Civil Engineering, 2019)
One of the most powerful modern methods of calculating complex building structures is the finite element method in the form of a displacement method for discrete systems, which involves the creation of a finite element model, that is, splitting the structure into separate elements within each of which the functions of displacements and stresses are known. On the basis of the displacement method and the methods of iterations and half-division, an algorithm for stability calculation of the first kind equilibrium form of compressed reinforced concrete columns with hinged fixing at the ends, considering the stiffness changing has been developed. The use of the above methods enables to determine the minimum critical load or stress at the first bifurcation and their stability loss corresponding form. The use of matrix forms contributes to simplification of high order stability loss equation. This approach enables to obtain the form of stability loss that corresponds to the critical load.